Otte Sperling den yngres latinske Leonora Christina-biografi (ca. 1690) - Olden-Jørgensen, Sebastian (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2023)
Sebastian Olden-Jørgensen: Otto Sperling the younger’s Latin biography of Leonora Christina (ca. 1690) Sebastian Olden-Jørgensen: The Danish antiquarian Otto Sperling the younger (1634‑1715) worked for most of his life on a manuscript titled ‘De foeminis doctis’, now in the collection of the Royal Library, shelfmark GKS 2110 quarto, which contained short biographies of a total of 1,399 learned women from all ages and nations (cf. Fund og Forskning, 2012, pp. 187‑212). One of these is Leonora Christina (1621‑1698), the daughter of Christian IV and his morganatic wife, Kirsten Munk, and a major figure in Danish literature thanks to her prison narrative Jammers Minde and her so-called ‘French Autobiography’. Sperling’s Latin biography focuses on her literary achievements and contains information not found elsewhere. It has been known to scholarship for generations, and a partial translation from the eighteenth century exists in manuscript, but the text has never been published, probably because it consists of 24 pieces distributed over 18 different pages between pp. 306 and 401 of vol. I of the manuscript. It is here edited and translated into Danish for the first time, and it is argued that Sperling composed it on the basis of a series of interviews with the ageing Leonora Christina after her release from prison in 1685. In other words, Sperling functioned as Leonora Christina’s ghostwriter, and the text should really be considered autobiographical and placed alongside the Jammers Minde and her French Autobiography as an authentic expression of her personality.